Analisis Manajemen Risiko Pada CV XYZ Dengan Menerapkan ISO 31000:2018 - Andreas Alessandro; Bima Aprianto S; Sri Andayani (CV. ITTC INDONESIA, 2024)
CV XYZ is a trading company that supplies mineral water with a marketing focus in Sumatra, especially Palembang. Even though operations are optimal, companies face business risks such as employee negligence, failure to achieve goals, and potential bankruptcy. This research aims to analyze risk management at CV XYZ using a qualitative case study approach. Data was collected through interviews and observations, with a focus on employee negligence, goal achievement, and bankruptcy risk. Based on ISO 31000:2018, risks are identified, assessed and addressed. High risks such as product defects and labor strikes require strong preventative measures, while low risks such as supply delays can be managed with light mitigation strategies. The research conclusions show that effective risk management through structured mitigation strategies and ongoing evaluation is critical to maintaining business continuity and increasing customer satisfaction. Recommendations include a comprehensive risk management program, improved quality control, supply chain optimization, employee development, insurance policy review, and environmental risk planning to ensure long-term business sustainability